Structural Analysis and Conformational Dynamics of STN1 Gene Mutations Involved in Coat Plus Syndrome - Amir, Mohd.; Mohammad, Taj; Kumar, Vijay; Alajmi, Mohammed F.; Rehman, Md. Tabish; Hussain, Afzal; Alam, Perwez; Dohare, Ravins; Islam, Asimul; Ahmad, Faizan; Hassan, Md. Imtaiyaz (Frontiers in Molecular Biosciences, 2019)
The human CST complex (CTC1-STN1-TEN1) is associated with telomere functions including genome stability. . We have systemically analyzed the sequence of STN, and performed structure analysis to establish of its association with the Coat plus (CP) syndrome. Many deleterious non-synonymous SNPs have been identified and subjected for structure analysis to find their pathogenic association and aggregation propensity. A 100 ns molecular dynamic simulation of WT, R135T and D157Y structures revealed significant conformational changes in the case of mutants. Hydrogen bond, secondary structure and principal component analysis further supporting the structural basis of STN1 dysfunction in such mutations. Free energy landscape analysis revealed the presence of multiple energy minima, suggesting R135T and D157Y mutations destabilize the STN1, and thus may be associated with the CP syndrome. Our study provides a valuable direction to understand the molecular basis of CP syndrome and offer a newer therapeutics approach to address CP syndrome.